1999
DOI: 10.1103/physrevb.60.r13941
|View full text |Cite
|
Sign up to set email alerts
|

Field-dependent specific heat inFe2VAland the question of possible3dheavy fermion behavior

Abstract: Specific heat measurements on Fe 2 VAl show the previously reported upturn in electronic specific heat coefficient (␥) to be sample dependent, and related to magnetic defects. These measurements, in temperatures as low as 0.6 K and magnetic fields up to 8 T, indicate the presence of Schottky anomalies arising from magnetic clusters having a moment 3.7 B. This result is in good agreement with theoretical estimates for Fe antisite defects in the material. The inherent ␥ϭ1.5Ϯ0.3 mJ/mol K 2 deduced from this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
80
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 19 publications
13
80
2
Order By: Relevance
“…From our Mössbauer data we can estimate for sc-Fe 2 VAl the required number of site exchanged Fe II/V pairs: to account for the broadening of the Mössbauer-line below T C it would require at least 6% Fe II on V sites. This value, which is more than one order of magnitude larger than the estimated level of Fe/V site exchanges for q-Fe 2 VAl of 0.3-0.4% [10,11], is inconsistent with the result of our neutron diffraction experiments, setting an upper limit of 3% Fe II on V sites. Therefore, we conclude that neither model proposed so far properly accounts for the Mössbauer spectra of Fe 2+x V 1−x Al, x≈0.…”
contrasting
confidence: 96%
See 2 more Smart Citations
“…From our Mössbauer data we can estimate for sc-Fe 2 VAl the required number of site exchanged Fe II/V pairs: to account for the broadening of the Mössbauer-line below T C it would require at least 6% Fe II on V sites. This value, which is more than one order of magnitude larger than the estimated level of Fe/V site exchanges for q-Fe 2 VAl of 0.3-0.4% [10,11], is inconsistent with the result of our neutron diffraction experiments, setting an upper limit of 3% Fe II on V sites. Therefore, we conclude that neither model proposed so far properly accounts for the Mössbauer spectra of Fe 2+x V 1−x Al, x≈0.…”
contrasting
confidence: 96%
“…Therefore, in Ref. 5 it has been speculated that the (magneto)resistivity of Fe 2 VAl reflects a mixture of electron excitation processes over the pseudogap and spin dependent scattering from impurities.Independently, on basis of specific heat and NMR-experiments it has been demonstrated that in Fe 2 VAl crystallographic disorder, assumed to be present in form of atomic site exchange between Fe and V atoms, substantially affects the ground state properties of this compound [10,11]. In particular, the anomalous low temperature specific heat has been attributed to ferromagnetic clusters with a density of 0.003-0.004/unit cell, consistent with the results from NMR experiments.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…7,[10][11][12][13][14] Consequently, the samples at x Ϸ 0 and ␦ Ϸ 0 are located at the brink of ferromagnetic order, close to the ferromagnetic quantum critical point, i.e., T C → 0. 6,8 Stimulated by these findings, theoretical work claimed Fe 2 VAl is a nonmagnetic semimetal with the pseudogap at the Fermi level. [15][16][17] The considerable mass enhancement of the conduction carriers was attributed to excitonic correlations 16 or spin fluctuations.…”
Section: Introductionmentioning
confidence: 94%
“…17 However, subsequent specific heat, C͑T͒, measurements in applied magnetic fields showed that the upturn in C / T at low temperatures results from a Schottky contribution of magnetic clusters in Fe 2 VAl. 8 The effects of off-stoichiometry have not been investigated quantitatively in the framework of nearly and weak ferromagnetism at x Ϸ 0 and ␦ Ϸ 0 yet. Another interesting aspect of Fe 2 VAl is its potential for application in thermoelectric devices, since off-stoichiometry and heattreatment procedures may results in an enhancement of the Seebeck coefficient.…”
Section: Introductionmentioning
confidence: 99%